Targeting B Lymphocytes Using Protein‐Functionalized Graphene Oxide. Issue 11 (4th August 2021) - Muzi, Laura; Seifert, Cécile; Soltani, Rym; Ménard-Moyon, Cécilia; Dumortier, Hélène; Bianco, Alberto
Abstract : The high surface area and the possibility of surface functionalization associated with a high biocompatibility endow graphene oxide with a great potential for biomedical applications. Although this material has been widely investigated for cancer therapy, it has been scarcely used for the treatment of autoimmune diseases. Herein, graphene oxide–lysozyme stable conjugates are prepared by a straightforward noncovalent functionalization approach. The complexes are able to selectively target a B lymphocyte cell model, which expresses a lysozyme‐specific B cell receptor. The results suggest the use of graphene oxide as a promising nanocarrier for the targeted therapy of B‐cell‐mediated autoimmune diseases, allowing overcoming the severe inconveniences associated with available B‐cell‐targeted therapies. Abstract : A graphene oxide–lysozyme stable conjugate is able to selectively target a B lymphocyte cell model expressing a lysozyme‐specific B‐cell receptor. Graphene oxide could be exploited for the targeted elimination of harmful B lymphocytes in autoimmune diseases and cancer, as alternative to the current B‐cell‐targeted therapies showing a variable efficacy and severe side effects.